Investigating radical cation chain processes in the electrocatalytic Diels–Alder reaction - Imada, Yasushi; Okada, Yohei; Chiba, Kazuhiro (Beilstein Journal of Organic Chemistry, 2018)
Single electron transfer (SET)-triggered radical ion-based reactions have proven to be powerful options in synthetic organic chemistry. Although unique chain processes have been proposed in various photo- and electrochemical radical ion-based transformations, the turnover number, also referred to as catalytic efficiency, remains unclear in most cases. Herein, we disclose our investigations of radical cation chain processes in the electrocatalytic Diels–Alder reaction, leading to a scalable synthesis. A gram-scale synthesis was achieved with high current efficiency of up to 8000%. The reaction monitoring profiles showed sigmoidal curves with induction periods, suggesting the involvement of intermediate(s) in the rate determining step.
Keywords: chain process; Diels–Alder reaction; electrocatalytic; radical cation; single electron transfer

(untitled) - Twilton, J.; Le, C.; Zhang, P.; Shaw, M. H.; Evans, R. W.; MacMillan, D. W. C. (Nat. Rev. Chem., 2017)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Skubi, K. L.; Blum, T. R.; Yoon, T. P. (Chem. Rev., 2016)

(untitled) - Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Kärkäs, M. D.; Porco, J. A., Jr; Stephenson, C. R. J. (Chem. Rev., 2016)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Yoshida, J.-i.; Shimizu, A.; Hayashi, R. (Chem. Rev., 2018)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Horn, E. J.; Rosen, B. R.; Baran, P. S. (ACS Cent. Sci., 2016)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Bawn, C. E. H.; Ledwith, A.; Shih-Lin, Y. (Chem. Ind., 1965)

(untitled) - Bell, F. A.; Crellin, R. A.; Fujii, H.; Ledwith, A. (J. Chem. Soc. D, 1969)

(untitled) - Carruthers, R. A.; Crellin, R. A.; Ledwith, A. (J. Chem. Soc. D, 1969)

(untitled) - Crellin, R. A.; Lambert, M. C.; Ledwith, A. (J. Chem. Soc. D, 1970)

(untitled) - Ledwith, A. (Acc. Chem. Res., 1972)

(untitled) - Lorenz, K. T.; Bauld, N. L. (J. Am. Chem. Soc., 1987)

(untitled) - Cismesia, M. A.; Yoon, T. P. (Chem. Sci., 2015)

(untitled) - Okada, Y.; Chiba, K. (Chem. Rev., 2018)

(untitled) - Ozaki, A.; Yamaguchi, Y.; Okada, Y.; Chiba, K. (ChemElectroChem, 2017)

(untitled) - Okada, Y.; Yamaguchi, Y.; Ozaki, A.; Chiba, K. (Chem. Sci., 2016)

(untitled) - Okada, Y.; Shimada, K.; Kitano, Y.; Chiba, K. (Eur. J. Org. Chem., 2014)

(untitled) - Yamaguchi, Y.; Okada, Y.; Chiba, K. (J. Org. Chem., 2013)

(untitled) - Okada, Y.; Nishimoto, A.; Akaba, R.; Chiba, K. (J. Org. Chem., 2011)

(untitled) - Imada, Y.; Yamaguchi, Y.; Shida, N.; Okada, Y.; Chiba, K. (Chem. Commun., 2017)

(untitled) - Kawamata, Y.; Yan, M.; Liu, Z.; Bao, D.-H.; Chen, J.; Starr, J. T.; Baran, P. S. (J. Am. Chem. Soc., 2017)

(untitled) - Horn, E. J.; Rosen, B. R.; Chen, Y.; Tang, J.; Chen, K.; Eastgate, M. D.; Baran, P. S. (Nature, 2016)

(untitled) - Gütz, C.; Stenglein, A.; Waldvogel, S. R. (Org. Process Res. Dev., 2017)

(untitled) - Gütz, C.; Bänziger, M.; Bucher, C.; Galvão, T. R.; Waldvogel, S. R. (Org. Process Res. Dev., 2015)

(untitled) - Reynolds, D. W.; Bauld, N. L. (Tetrahedron, 1986)

(untitled) - Lin, S.; Ischay, M. A.; Fry, C. G.; Yoon, T. P. (J. Am. Chem. Soc., 2011)

(untitled) - Ischay, M. A.; Ament, M. S.; Yoon, T. P. (Chem. Sci., 2012)